Systematic review of behaviour change techniques to promote participation in physical activity among people with dementia - Nyman, Samuel R.; Adamczewska, Natalia; Howlett, Neil (British journal of health psychology, 2018)
Purpose The objective of this study was to systematically review the evidence for the potential promise of behaviour change techniques (BCTs) to increase physical activity among people with dementia (PWD). Methods PsychINFO, MEDLINE, CINAHL, and the Cochrane Central Register of Controlled Trials databases were searched 01/01/2000–01/12/2016. Randomized controlled/quasi‐randomized trials were included if they recruited people diagnosed/suspected to have dementia, used at least one BCT in the intervention arm, and had at least one follow‐up measure of physical activity/adherence. Studies were appraised using the Cochrane Collaboration Risk of Bias Tool, and BCTs were coded using Michie et al., 2013, Annals of Behavioral Medicine, 46, 81. taxonomy. Intervention findings were narratively synthesized as either ‘very promising’, ‘quite promising’, or ‘non‐promising’, and BCTs were judged as having potential promise if they featured in at least twice as many very/quite promising than non‐promising interventions (as per Gardner et al., 2016, Health Psychology Review, 10, 89). Results Nineteen articles from nine trials reported physical activity findings on behavioural outcomes (two very promising, one quite promising, and two non‐promising) or intervention adherence (one quite promising and four non‐promising). Thirteen BCTs were used across the interventions. While no BCT had potential promise to increase intervention adherence, three BCTs had potential promise for improving physical activity behaviour outcomes: goal setting (behaviour), social support (unspecified), and using a credible source. Conclusions Three BCTs have potential promise for use in future interventions to increase physical activity among PWD. Statement of contribution What is already known on this subject? While physical activity is a key lifestyle factor to enhance and maintain health and wellbeing amongst the general population, adults rarely participate in sufficient levels to obtain these benefits. Systematic reviews suggest that specific behaviour change techniques can increase physical activity, although one review suggested that self‐regulatory techniques may be counterproductive when promoting physical activity among older people. Until now, no systematic review has been conducted to assess which behaviour change techniques may be associated with greater participation in physical activity among people with dementia. What does this study add? Interventions showed mixed promise for increasing physical activity and little effect on participant adherence. Goal setting (behaviour), social support (unspecified), and using a credible source are promising approaches. No technique showed promise for increasing adherence to physical activity interventions among people with dementia.